Ring‐Opening Metathesis Polymerization of Norbornene‐Based Monomers Obtained via the Passerini Three Component Reaction. Issue 9 (1st March 2021) - Barther, Dennis; Moatsou, Dafni
Abstract: Ring‐opening metathesis polymerization is a robust method to synthesize a variety of polymers by using ring‐strained molecules as monomers, e.g., norbornenes. However, the synthesis of monomers with multiple functional groups remains a challenge, albeit peptide functional norbornenes have previously been used. Here, the Passerini three component reaction is exploited to synthesize norbornenes with two variable functional groups varying in bulkiness and distance from the polymerizable alkene. The results indicate that the functional groups do not affect the kinetics of the polymerization, whereas the length of the linker has a minor effect. Furthermore, a diblock‐type copolymer is synthesized in a one‐pot fashion, also indicating good control of the polymerization process. The thermal properties of all polymers are evaluated, highlighting the effect of monomer composition. This synthetic approach can be transferred to a variety of compounds, thus promising highly diverse polymers with complex compositions and architectures. Abstract : Multifunctional norbornene monomers are synthesized via the Passerini three component reaction and undergo ring‐opening metathesis polymerization in a controlled manner. By evaluating the kinetics of the homopolymerizations, random and diblock‐like copolymers are prepared. Furthermore, the influence of monomer characteristics on the polymer thermal properties is examined.